THE UNKNOWN FACE OF KUSAMA YAYOI – JAPANESE ARTIST AND WRITER - Pachciarek, Paweł (Porównania, 2016)
Even though the interest in Yayoi Kusama has been growing since the end of the last century, there are still undiscovered aspects of her works which are addressed in this paper. I try to show how her works from the early period can be interpreted in the context of tradition and the key assumptions of Japanese art. I proceed to discuss the literary output of the artist which now seems to go unnoticed by a wider audience. To conclude, I will answer the question of what brings together the experiences of Kusama and the story of Alice in Wonderland.